Effects of long-term ammonia and heat stress on growth performance, antioxidant and immunity of wild and breeding juvenile rice field eel (Monopterus albus) - Li, Muyan; Huang, Weiwei; Zhao, Yifan; Yuan, Quan; Yang, Hang; Lv, Weiwei; Zhou, Wenzong (Frontiers in Marine Science, 2024)
This study aimed to evaluate the impacts of wild and breeding juvenile rice field eel under conditions of ammonia and heat stress. The growth performance (FBW, WGR, SGR, and FCR) of 360 wild (24.22 ± 0.30 g) and 360 breeding (24.16 ± 0.27 g) strains was significantly hindered by ammonia and heat stress. The inhibitory effects were more obvious when the two stresses were combined. The growth performance and survival rates of the breeding strains outperformed that of the wild strains under identical stress conditions, this was explained by the expression of the growth-related gene (gh). They have increased the enzyme activity (CAT and GSH-Px) and expression of immune-related genes (cat, gpx3, and hsp90α) in response to oxidative stress. However, the results of certain indicator enzymes indicate the presence of oxidative damage in their tissues. The presence of an inflammatory response in the tissues was suggested by the up-regulation of genes associated with pro-inflammatory cytokines (il-1β and il-8) and the down-regulation of genes related to anti-inflammatory cytokines (il-10). Additionally, the presence of tissue damage was shown by the up-regulation of genes connected to apoptosis (cas2, cas8, and cas9) and the down-regulation of genes connected to tight junctions (zo-1). Nevertheless, it is noteworthy that breeding strains exhibited superior adaptability to ammonia and heat stress in comparison to wild strains.